Antibacterial effect of cinnamon (Cinnamomum verum) against bacteria isolated from cats with otitis externa - Mokhtar, Aimi Najwa (2016)
Thirty (30) ear swab samples were taken from cats in a private clinic. The samples were then cultured on blood agar for isolation and identification of bacteria. Antibacterial effect of Cinnamomum verum was determined by conducting antibiotic sensitivity test (AST), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) against bacteria isolated from the samples which include Staphylococcus pseudintermedius, Staphylococcus intermedius, Staphylococcus hyicus, Enterococcus faecalis, Corynebacterium ulcerans, Bacillus sp. and Aggregatibacter actinomycetemcomitans. Cinnamon paste was prepared by mixing cinnamon powder with sterile distilled water for the usage in the tests. All of the bacteria tested showed susceptibility towards the cinnamon paste and some showed resistance towards some of the commercially used antibiotics such as marbofloxacin, doxycycline and enrofloxacin. There were significant differences in the diameter of inhibition zone (DIZ) of each bacterium tested against different antibiotics and the cinnamon paste (p = 0.000). The MIC test result of the cinnamon paste showed its maximum activity values that range from 0.03 to 1.00g/ml. The MBC test shown that the concentration of cinnamon paste that could have inhibited the growth or kill the bacteria tested was ranges from 0.03 to 0.67g/ml. Based on the test results, it suggested that C. verum do have antibacterial effect against bacteria isolated from cats with otitis externa and it may be used as the alternative treatment for such cases.